Design and Analysis of 8-Bit Low Power ALU in 45 nm Using GDI Technique - Wong, Siong Hui; Ruslan, Siti Hawa (Evolution in Electrical and Electronic Engineering, 2021)
Arithmetic Logic Unit (ALU) is the main part inside a computer’s central processing unit (CPU) that performs arithmetic and logic operations. Since the technology grows faster, power dissipation in ALU becomes vital to be reduced. So, Gate Diffusion Input (GDI) is introduced because less transistors are used to achieve low power dissipation. The limitation of the GDI technique is poor voltage swing output, but it can be solved by modifying the GDI cell and adding some transistors. In this paper, Mentor Graphics software is used to build the 8-bit ALU in 45 nm using the GDI technique with the power supply of 1.0 V. Results show that the GDI technique will help minimize power dissipation, time delay, and area.